Assessment of priorities of construction of high-speed rail in the Czech Republic in terms of impacts on internal and external integration - Vilém Pařil; Milan Viturka (Review of Economic Perspectives, 2020)
The priorities assessment for the planned construction of high-speed rail/HSR in the Czech Republic in terms of impacts on internal and external integration is a though-provoking topic not only from the technical and economic, but also from the social and geographical point of view. Its primary basis is the application of the gravity model, according to which the planned route C Prague-Wien has the most significant potential in passenger transport. Then following routes are A Prague-Berlin, B Prague-München, and D Brno-Katowice. Subsequently, the likely impacts generated by a significant improvement in the quality parameters and hence the competitive position of rail transport were assessed, including the potential for shifting part of the demand from the road and air transport to HSR. Overall, however, it can be stated that the potential impacts of the HSR on the growth of passenger transport in the Czech Republic will not be essential. To perceive the regional impacts of HSR construction, analyses of selected indicators (population density per km2, GDP per capita, unemployment rate) by NUTS 3 regions for the period 2007-2017 were also carried out. From the strategic point of view, the research results did not confirm that the planned construction of the HSR primarily stimulates convergence tendencies in regional development as the main priority of EU regional policy. Rather, it seems more likely that the HSR will stimulate the extraction of economic activity from "rural" regions in favour of metropolitan regions.
Keywords: O18; R42; 330; gravity model; high-speed rail / HSR; integration; metropolises; project